2020
DOI: 10.1016/j.healun.2020.02.008
|View full text |Cite
|
Sign up to set email alerts
|

A current era analysis of ABO incompatible listing practice and impact on outcomes in young children requiring heart transplantation

Abstract: BACKGROUND: Heart transplantation from ABO incompatible (ABOi) donors has evolved into a progressively accepted therapy in young children. We assessed the recent practice of ABOi listing impact on waitlist and post-transplant outcomes. METHODS: Using the Pediatric Heart Transplant Society registry, we compared clinical presentation, waitlist parameters, and post-transplant survival of children < 2 years of age listed for ABOi vs ABO compatible (ABOc) heart transplant between January 2010 and June 2018 with sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Importantly, ABOi PHT did not affect early or long-term survival or the incidence of rejection and led to a significant decrease in waitlist time for blood group O recipients. These observations were further validated by Urschel and colleagues 13 using the Pediatric Heart Transplant Society registry. These authors also demonstrated that children initially listed for compatible transplantation and changed to ABOi had higher 1-year mortality, which likely reflects precarious clinical status, worsening clinical condition, and need for extracorporeal membrane oxygenation.…”
Section: Improving Pht Outcomesmentioning
confidence: 61%
“…Importantly, ABOi PHT did not affect early or long-term survival or the incidence of rejection and led to a significant decrease in waitlist time for blood group O recipients. These observations were further validated by Urschel and colleagues 13 using the Pediatric Heart Transplant Society registry. These authors also demonstrated that children initially listed for compatible transplantation and changed to ABOi had higher 1-year mortality, which likely reflects precarious clinical status, worsening clinical condition, and need for extracorporeal membrane oxygenation.…”
Section: Improving Pht Outcomesmentioning
confidence: 61%
“…24,25 We attribute this to the fact that prior studies, including a large, recent, multicenter study of the Pediatric Heart Transplant Study and/or Society, have only assessed posttransplant survival of ABO blood type incompatible patients as a whole without stratifying by diagnoses. 26 Therefore, they may not have identified ABO blood type incompatibility as a risk factor specific to patients with CHD such as in this study. There are studies which note a predilection toward listing more ill children as ABO blood type incompatible, and it may be desirable to transplant the patient sooner, despite higher posttransplant risk of mortality.…”
Section: Commentmentioning
confidence: 85%
“…29 ABO-incompatible OHT has been successful among children and neonates and is now common practice in children under 2 years of age, increasing from 49% in 2010 to 72% in 2017. 23,29,30 An important implication of ABO-incompatible OHTs becoming commonplace is that it alleviates the undue burden of competition for donor organs among patients with blood group O. This is reflected in a significantly shorter waitlist time for blood group O patients when ABO-incompatible organs are accepted.…”
Section: Shortage Of Hearts For Pediatric Transplantmentioning
confidence: 99%